Learning Climate Perceptions as a Determinant of Employability: An Empirical Study Among European ICT Professionals - Van der Heijde, Claudia M.; Van der Heijden, Beatrice I. J. M.; Scholarios, Dora; Bozionelos, Nikos; Mikkelsen, Aslaug; Epitropaki, Olga; Marzec, Izabela; Jędrzejowicz, Piotr; Looise, Jan C.; , the Indic@tor Study Group (Frontiers in Psychology, 2018)
This study investigated the role of age in the relationship between perceptions of learning climate and self- and supervisor-rated employability among European Information and Communication Technology (ICT) professionals. The psychological climate for learning was operationalized by three indicators, namely the perceptions that employees have of the learning value of their job, supervisor support for learning, and the organizational support for learning. As hypothesized, a Structural Equation Model demonstrated that the relationship between age and perceptions of learning climate was negative. The model also showed a strong positive relationship between learning climate and self-reported and supervisor-rated employability. Furthermore, learning climate perceptions appeared important for employability irrespective of life or career stage. An explorative bootstrapping-based test suggested that older workers with managerial responsibilities profit less from psychological learning climate for self-reported and supervisor-rated employability than older workers at non-managerial levels. These findings have important implications for human resource practices that aim to increase lifelong employability.